Push back - Spafford-Fitz, Karen, 1963- (SideStreets., 2019)
After living on the streets and being badly beaten, Zaine is back at his aunt's, but is angry after his mother breaks another promise to take him back, so he flees and trashes a storage shed, injuring the owner as he runs away.